Prevalence of Chlamydia trachomatis and other micro-organisms in women seeking abortions in Pittsburgh, Pennsylvania, United States of America. - Amortegul, A J (1986)
The prevalence of Chlamydia trachomatis, Ureaplasma urealyticum, Mycoplasma hominis, group B streptococcus, herpes simplex virus, and Neisseria gonorrhoeae from cervical cultures obtained from 210 women seeking abortion in Pittsburgh, Pennsylvania, United States of America was 9.3%, 72.9%, 25.2%, 4.3%, 0.9%, and 0.9% respectively. Cultures from 40/203 (19.7%) patients failed to produce any of these organisms. C trachomatis isolation was not associated with age, race, marital status, average family income, number of sexual partners, history of gonorrhoea or syphilis, or previous pregnancies, live births, or abortions, and 82.4% of women with chlamydial infections had had no urogenital symptoms in the preceding six months. The highest concentration of U urealyticum was 10(5) colour changing units (ccu)/ml, and about half of the positive ureaplasma cultures produced less than 10(3) ccu/ml of this organism. Screening for C trachomatis, is encouraged to prevent neonatal morbidity and the common complication of pelvic inflammatory disease after abortion.